Absence of keratin 8 or 18 promotes antimitochondrial autoantibody formation in aging male mice. Issue 12 (23rd September 2015) - Toivola, Diana M.; Habtezion, Aida; Misiorek, Julia O.; Zhang, Linxing; Nyström, Joel H.; Sharpe, Orr; Robinson, William H.; Kwan, Raymond; Omary, M. Bishr
ABSTRACT: Human mutations in keratin 8 (K8) and keratin 18 (K18), the intermediate filament proteins of hepatocytes, predispose to several liver diseases. K8‐null mice develop chronic liver injury and fragile hepatocytes, dysfunctional mitochondria, and Th2‐type colitis. We tested the hypothesis that autoantibody formation accompanies the liver damage that associates with K8/K18 absence. Sera from wild‐type control, K8‐null, and K18‐null mice were analyzed by immunoblotting and immunofluorescence staining of cell and mouse tissue homogenates. Autoantibodies to several antigens were identified in 81 % of K8‐null male mice 8 mo or older. Similar autoantibodies were detected in aging K18‐null male mice that had a related liver phenotype but normal colon compared with K8‐null mice, suggesting that the autoantibodies are linked to liver rather than colonic disease. However, these autoantibodies were not observed in nontransgenic mice subjected to 4 chronic injury models. The autoantigens are ubiquitous and partition with mitochondria. Mass spectrometry and purified protein analysis identified, mitochondrial HMG‐CoA synthase, aldehyde dehydrogenase, and catalase as the primary autoantigens, and glutamate dehydrogenase and epoxide hydrolase‐2 as additional autoantigens. Therefore, absence of the hepatocyte keratins results in production of anti‐mitochondrial autoantibodies (AMA) that recognize proteins involved in energy metabolism and oxidative stress, raising the possibility that AMA may be found in patients with keratin mutations that associate with liver and other diseases.—Toivola, D. M., Habtezion, A., Misiorek, J. O., Zhang, L., Nyström, J. H., Sharpe, O., Robinson, W. H., Kwan, R., Omary, M. B. Absence of keratin 8 or 18 promotes antimitochondrial autoantibody formation in aging male mice. FASEB J. 29, 5081–5089 (2015). www.fasebj.org